IPTEKS PENGENDALIAN INTERNAL TERHADAP PEREKAMAN SURAT PEMBERITAHUAN TAHUNAN (SPT) PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MANADO - Amin, Nabilah N.R.; Latjandu, Lady Diana (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
KPP Pratama Manado is a tax administration agency in the Manado area under the auspices of the Indonesian Ministry of Finance. The main task of KPP Pratama Manado is to carry out the main duties of the Directorate General of Taxes in collecting State revenues from the Taxation sector. To achieve the best service, recording annual notification letters (SPT) on taxpayers is one of the important roles in reporting, receiving or deduction. This study aims to determine the internal control of SPT recording at KPP Pratama Manado. Internal controls will run according to regulations if implementing COSO internal controls, including the control environment, risk assessment, control activities, information and communication, and monitoring. The results of the study indicate that the ability of KPP Pratama Manado in processing and recording Annual Tax Returns is quite effective, but delays in reporting will often occur.Keywords: Tax, SPT, recording, internal control, procedures